Association of Fecal Microbiota with Irritable Bowel Syndrome-Diarrhea and Effect of Traditional Chinese Medicine for Its Management. (30th September 2021) - Yang, Fang; Wu, Jiaqi; Ye, Ning-Yuan; Miu, Jing; Yan, Jing; Liu, Li-Na; Ye, Bai
Abstract : Changes in intestinal microbiota have been linked to the development of diarrhea predominant irritable bowel syndrome (IBS-D). In order to better elucidate the relationship between intestinal microbiota changes and IBS-D, we compared fecal microbiota of IBS-D rats and healthy control using pyrosequencing of bacterial 16S rRNA gene targeted. Furthermore, we explored the effects of different traditional Chinese medicine (TCM) on intestinal microbiota of IBS-D in dose-dependent manner. Our results showed that there was no significant difference in fecal microbial community diversity among the healthy control group, IBS-D rats and IBS-D rats treated with traditional Chinese medicine, but the fecal microbial composition at different taxonomic levels have changed among these groups. Interestingly, the weight of IBS-D rats treated with moderate doses (13.4 g/kg) of TCM increased significantly, and the diarrhea-related symptoms improved significantly, which may be related to the enrichment in Deferribacteres, Proteobacteria, Tenericutes, Lachnospiraceae, and Ruminococcaceae and the reduction in Lactobacillus in fecal samples.